Soil characteristic and shallot growth with gypsum and zeolite amendments in irrigated saline Alfisol and Inceptisol - Rahayu Rahayu; Jauhari Syamsiyah; Livia Dewi (Brawijaya University, 2021)
Salinity of soil and irrigation is a factor that may cause a decrease in shallot productivity, so it requires efforts with amendments. This research aimed to determine the effect of gypsum and zeolite amendments on soil and shallot growth with saline irrigation. A pot experiment was conducted in the field using a completely randomized design with three factors. The first factor was two soil types (Alfisol and Inceptisol); the second factor was three shallot cultivars (Brebes, Purbalingga, and Pemalang); and the third factor was two types of soil amendments. The results showed that gypsum and zeolite reduced pH, sodium adsorption ratio (SAR), electric conductivity paste (ECp) and Na of the soils studied. Gypsum and zeolite increased the uptake of N, P and K by shallot plants. The increase of N uptake by applying gypsum on Inceptisol was more effective to Brebes and Purbalingga cultivars than Pemalang cultivar. Gypsum increased the diameter and number of bulbs in Inceptisol. Zeolite and gypsum increased bulb weight of Purbalingga cultivar in Alfisol.